Steganography Method Using Hartley Transform - Козін, Олександр Борисович; Козин, Александр Борисович; Alexander Kozin, Alexander B.; Папковська, Ольга Борисівна; Папковская, Ольга Борисовна; Papkovskaya, Olga B.; Козіна, Марія; Козина, Мария; Kozina, Mariia (My University, 2016)
This paper presents the method of steganography that organizes a covert communication channel, by embedding the additional information in the frequency domain. The proposed method of embedding the additional information in the coefficients of the discrete Hartley transforms, due to unavailability of a complex data structures. It has the symmetry of the formulas the direct and the inverse transform that's why it ensures high computational efficiency in the processing of real data type.
Kozin A. Steganography Method Using Hartley Transform / Alexander Kozin, Olga Papkovskaya, Mariia Kozina // Modern Problems of Radio Engineering, Telecommunications, and Computer Science : XIIIth 2016 International Conference (Lviv-Slavsko, February 23 – 26, 2016). - Lviv, 2016. - p. 473 -475. = Сучасні проблеми радіоелектроніки, телекомунікацій, комп'ютерної інженерії : матеріали Міжнар. конф.TCSET’2016 ( Львів-Славсько, 23-26 лютого 2016 р.). - Львів, 2016. - с. 473-475.
Keywords: Hidden data; Hartley transform; Digital images; Binary sequences; приховані дані; перетворення Хартлі; цифрові зображення; бінарні послідовності; скрытые данные; преобразование Хартли; цифровые изображения; бинарные последовательности